PENANAMAN NILAI-NILAI KARAKTER PADA SISWA SEKOLAH DASAR MELALUI CERITA RAMAYANA - Sukiningsih, Ni Wayan (Adi Widya: Jurnal Pendidikan Dasar, 2019)
This paper aims to describe the character values of elementary school students through Ramayana stories. Character education in elementary school is an effort to build character of elementary school student. There is a shift in values regarding norms of decency, ethics and morality. Moral degradation can be regarded as an indicator of the weak understanding of religious values. In Hindu Literature, especially in Itihasa, in which there is a Ramayana story, this story is full of character values. In the classroom learning the teacher at least tucked the story with the goal of students can adopt the character of every character in the Ramayana story that can make students become comfortable in following the lessons and can implement in every aspect of life, and is expected to motivate and provide new paradigm in the effort shaping the character of the young generation.